Meningococcal carriage and transmission dynamics in college students in Louisville, Kentucky - Forest W. Arnold; Leslie Wolf Parrish; Subathra Marimuthu; Jamie Findlow; Angela Quinn; Vidyulata Salunkhe; Daniya Sheikh; Phillip Bressoud; T’shura Ali; Dawn Balcom; Mohammad Ali; Ryan S. Doster; et al. (PLoS ONE, 2026)
Background Neisseria meningitidis is a cause of meningitis and outbreaks of it among young adults, especially college students. Rates of nasopharyngeal colonization and prevalence of specific capsular groups vary with age, geography as well as time, and may be influenced by meningococcal vaccination. The objective of this study was to measure the change in colonization rate, and define which meningococcal genogroups were present, in college students over a 3-month semester. Methods This was a prospective, longitudinal cohort study with sequential oropharyngeal swabbing among college students at the University of Louisville (UofL) in Louisville, Kentucky from August to November 2022. Participants were ≥18 years of age and were enrolled within 48 hours of moving to campus-affiliated housing. Oropharyngeal swabs were collected at enrollment, one month and at three months. Samples were screened for N. meningitidis , and isolates were characterized using phenotypic and genotypic methods. Behavior questionnaires were obtained at each visit to identify risk factors for N. meningitidis colonization. Results A total of 1047 participants were seen initially, of whom 821 attended all three visits. The baseline colonization rate was 3.5% followed by 3.9% after one month and 5.7% after three months. The genogroups of recovered isolates were capsule null (48%), B (38%; of which 11% were expressing capsule) and E (12%). No genogroup ACWY isolates were recovered. A total of 36% of participants had a history of receiving at least one MenB vaccine dose and 74% had a history of receiving at least one MenACWY vaccine. Risk factors for N. meningitidis nasopharyngeal carriage included being a second-year student, living on campus for the second year, smoking/vaping, kissing and sexual contact. Conclusions An increase in N. meningitidis colonization over the 3-month semester was observed from 3.5% to 5.7%. The overall proportion of student carriers was significantly lower, and there were no genogroup A, C, W or Y strains isolated compared to studies conducted prior to the availability of meningococcal vaccines and the COVID-19 pandemic. However, genogroup B carriage, transmission and acquisition were almost identical to pre-COVID pandemic studies. This study reinforces the importance of periodic epidemiological monitoring of carriage as well as disease.